The Lived Experiences of Adolescents Born in the 2000s Engaged in Opposite-Sex Relationships - Akhtari , Negin; Honarparvaran , Nazanin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore and interpret the lived experiences of adolescents born in the 2000s who are engaged in opposite-sex relationships, focusing on the psychosocial, emotional, and cultural dynamics that shape these relationships.Methods and Materials: This qualitative study was conducted using a grounded theory design to capture the subjective experiences of adolescents. The study population consisted of high school, pre-university, and undergraduate students in Shiraz, Iran, who were born in the 2000s and had been involved in opposite-sex relationships. Participants were selected through purposive sampling until theoretical saturation was achieved, resulting in a final sample of ten adolescents (five females and five males). Data were collected using in-depth semi-structured interviews and analyzed according to Anselm Strauss and Juliet Corbin’s three-stage coding approach (open, axial, and selective coding). Trustworthiness was enhanced through member checking, peer debriefing, negative case analysis, and maintaining a detailed audit trail. Ethical approval was obtained from the Islamic Azad University Ethics Committee, and informed consent was secured from all participants.Findings: The analysis revealed eleven axial categories capturing the core dynamics of these adolescents’ experiences: identity and future concerns, generational conflict and family pressure, factors of attraction and relationship maintenance, psychological and emotional effects of relationships, influence of family role models, socio-cultural changes, relationship dynamics and attraction patterns, coping mechanisms against pressure, psychological consequences of relationships, normative and cultural shifts, and the impact of future concerns on relationships. The emerging core category reflected adolescents’ negotiation of autonomy and identity within relationships while managing socio-cultural contradictions, emotional vulnerabilities, and aspirations for personal growth.Conclusion: Adolescent opposite-sex relationships constitute complex psychosocial phenomena shaped by intersecting personal, familial, and cultural forces. These relationships serve as arenas for identity exploration and emotional development, yet also expose adolescents to psychological risks, highlighting the need for supportive educational and counseling interventions.